2014
DOI: 10.1089/ten.tea.2013.0107
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold Architecture Controls Insulinoma Clustering, Viability, and Insulin Production

Abstract: Recently, in vitro diagnostic tools have shifted focus toward personalized medicine by incorporating patient cells into traditional test beds. These cell-based platforms commonly utilize two-dimensional substrates that lack the ability to support three-dimensional cell structures seen in vivo. As monolayer cell cultures have previously been shown to function differently than cells in vivo, the results of such in vitro tests may not accurately reflect cell response in vivo. It is therefore of interest to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…97 The spun fibers offer the possibility of fabricating scaffolds with a high surface to volume ratio, adaptable porosity properties, and applicability for a broad spectrum of materials. 97,98 Researchers used this relatively simple technique to produce polymer fibers from PLA, 99101 PVA, 53,99,100,102 PCL, 53,96,103,104 polyglecaprone (PGC), 96 PEOT/PBT, 90 gelatin, 105 polyethersulfone, 106,107 silk fibroin, and collagen. One disadvantage of this fabrication method might be the difficulty of scaling up these scaffolds to allow therapeutic human dosages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…97 The spun fibers offer the possibility of fabricating scaffolds with a high surface to volume ratio, adaptable porosity properties, and applicability for a broad spectrum of materials. 97,98 Researchers used this relatively simple technique to produce polymer fibers from PLA, 99101 PVA, 53,99,100,102 PCL, 53,96,103,104 polyglecaprone (PGC), 96 PEOT/PBT, 90 gelatin, 105 polyethersulfone, 106,107 silk fibroin, and collagen. One disadvantage of this fabrication method might be the difficulty of scaling up these scaffolds to allow therapeutic human dosages.…”
Section: Resultsmentioning
confidence: 99%
“…108 Blackstone et al actually showed a positive correlation between increased fiber diameter and inter-fiber distance with viability and function of the seeded cells. 105 They produced an electrospun scaffold from gelatin as a 3D cell culture platform. 105 Mostly, the electrospinning technique was applied for the fabrication of 3D cell culture templates to achieve enhanced differentiation of human adipose tissue-derived stem cells (hADSC) and human-induced pluripotent stem cells (hiPSC) into ISC 53,99,101103,106,107 but also for the in vivo transplantation of murine islets on electrospun PCL/PGC to the intrarenal transplantation site, with greater proliferation and functional output than the control without a scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of scaffolds has great effects on b cell viability and functionality. For instance, small-diameter, densely packed nanofibrous scaffolds can better promote the formation of large, round cell clusters and enhanced insulin production, as compared with large-diameter fibers (Blackstone et al, 2014). In another example, adipose stem cells seeded in a 3D biodegradable scaffold composed of natural polymers dextran and gelatin can effectively differentiate to islet-like clusters expressing islet-specific hormones (e.g.…”
Section: Other Methodsmentioning
confidence: 99%
“…[ 164 ] In immortalized cell line culture, fine control of gelatin fiber diameter and spacing can control 3D aggregation and insulin production from the β‐cell organoids. [ 165 ] In a unique layer‐by‐layer coating technique with alternating coatings of gelatin and fibronectin, mouse β‐cells formed tightly formed spheroids with increased GSIS, upregulated glucose transporter genes, and upregulated expression of connexin 36 gap junctions for improved synchronization of insulin secretion. [ 166 ] Gelatin has also be grafted with proteins necessary for differentiation (i.e., Activin A), which allows for continued presentation of the protein during hPSC differentiation and improved differentiation efficiency to the pancreatic progenitor stage.…”
Section: Engineered Biomaterials For β‐Cell Organoidsmentioning
confidence: 99%